LITERASI DIGITAL MATEMATIS DALAM MENYELESAIKAN SOAL PMRI KONTEKS WISATA PALEMBANG - Hasanah, Uswatun; Zulkardi, Zulkardi; Susanti, Ely (Universitas PGRI Sumatera Barat, 2023)
This type of research is a descriptive study with a qualitative approach that aims to describe students’ mathematical digital literacy skills in solving PMRI questions in the Palembang tourism context. This research was conducted because mathematical digital literacy is an important thing for students to have. In this study, test questions were distributed to determine students mathematical digital,literacy skills. The subjects in this study were grade VI Elementary School students. The implementation procedure in this study consisted of three stages, namely the preparation stage, the implementation stage, and the data analysis stage. Data collection techniques in this study were test and interviews. While the data analysis techniques in this study were data reduction, data presentation, and drawing conclutions. Based on the results of research representative with three student subjects, the aspects that most often appears are communication literacy, visual literacy and technological literacy. Meanwhile, aspects that rarely appear are information literacy and media literacy.